Compound heterozygous KCTD19 variants in a man with isolated nonobstructive azoospermia - Yuki Muranishi; Yuko Katoh‐Fukui; Atsushi Hattori; Yoshitomo Kobori; Akiyoshi Osaka; Hiroshi Okada; Toshiyuki Iwahata; Masafumi Kon; Nobuo Shinohara; Maki Fukami (Reproductive Medicine and Biology)
Abstract Case A 40‐year‐old Japanese man with nonobstructive azoospermia (NOA) was found to carry rare variants in KCTD19, a newly identified causative gene for spermatogenic failure. This patient was identified through mutation screening of KCTD19 in 97 men with etiology‐unknown isolated NOA. Outcome The patient had two heterozygous variants in KCTD19 that affect consensus sequences of splice‐donor sites [c.300+2T>A and c.2667C>T (p.E889E)]. Both variants were predicted to cause exon skipping. Long‐read sequencing confirmed the compound heterozygosity of the variants. The patient exhibited small testes and a mildly elevated level of follicle‐stimulating hormone but no other phenotypic abnormalities. Testicular histology showed borderline findings between spermatocyte maturation arrest and severe hypospermatogenesis. Conclusion These results provide evidence that biallelic loss‐of‐function variants of KCTD19 represent rare causes of isolated NOA.